Effect of Bloodletting at Shaoshang and Shangyang Acupuncture Points on Outcome and Prognosis of Severe Community-Acquired Pneumonia in the Elderly. (26th October 2021) - Fu, Yuefeng; Yang, Zhe; Cai, Yangping; Liu, Hongshuan; Li, Shuo; Kou, Nan; Wu, Jingqin; Zhang, Qing
Abstract : Objectives . The aim of this study was to explore, whether treatment with bloodletting at Shaoshang and Shangyang acupuncture points would affect therapy outcome and prognosis for severe community-acquired pneumonia (SCAP) in the elderly. Methods . A total of 62 patients, who met the diagnostic criteria for SCAP, were enrolled in the study and randomly divided into two groups, i.e., treatment group (n = 31 ) and control group (n = 31 ). All patients received a therapy according to the Chinese Clinical Practice and Expert Consensus of Emergency Severe Pneumonia from 2016. In addition to that, a bloodletting at Shaoshang (LU11) and Shangyang (LI1) acupuncture points was applied for the treatment group. This intervention was repeated for three times (ones daily), bloodletting a volume of 2-3 ml at each time point. Differences in a main index of clinical efficacy, body temperature (T), respiratory rate (RR), heart rate (Hr), white blood cell count (WBC), neutrophil percentage (N%), and C-reactive protein level (CRP) as well as different scores (CURB-65 score, SOFA score, and Apache II score) were compared between groups. Moreover, the 28-day mortality was compared between treatment and control group. The statistical methods involved in carrying out the current study include t -test, Wilcoxon test, and chi-square test. Results . The clinical effective rate of the treatment group was 82.9%, which was significantly higher than the 17.1% in the control group (P < 0.05 ). After finishing the intervention, the treatment group showed significantly lower T (37.28 ± 0.54 vs. 37.82 ± 0.81 ), RR (20.06 ± 2.67 vs. 23.71 ± 6.85 ), Hr (81.71 ± 10.38 vs. 93.84 ± 15.39 ), CUBR-65 score (2.16 ± 0.74 vs. 3.03 ± 0.98 ), and SOFA score (5.84 ± 3.83 vs. 8.16 ± 4.2 ) compared to the control group (P < 0.05 ). The 28-day mortality rate of the treatment group was significantly lower than in the control group (12.9% vs. 45.2%, P = 0.05 ). Conclusions . Bloodletting at Shaoshang and Shangyang acupuncture points can support improving the clinical treatment efficacy for SCAP and reduce the 28-day mortality rate in the elderly.